(untitled) (International Journal of Environmental Sciences, 2025)
Plastic pollution represents one of the most pressing environmental challenges of the 21st century, with polyethylene (PE) being among the most persistent polymers due to its hydrophobic surface properties and high molecular weight characteristics. This comprehensive study investigates the LDPE biodegradation potential using extracellular enzymes produced by four indigenous bacterial strains: Cytobacillus firmus, Priestia flexa, and Stutzerimonas stutzeri,. LDPE sheets were subjected to controlled incubation with these bacterial isolates for 30 days under optimized laboratory conditions. Biodegradation assessment was conducted through multiple analytical approaches including gravimetric weight loss analysis, surface hydrophobicity modifications, Fourier-transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). The bacterial strains demonstrated significant extracellular enzyme activities including laccase, lipase, and esterase, with corresponding measurable increases in carbonyl index values and observable surface erosion patterns. Results indicate that synergistic enzymatic action facilitates polymer oxidation and subsequent fragmentation processes, highlighting a promising biological approach for sustainable plastic waste mitigation strategies in environmental biotechnology applications.